THE RELATIONSHIP BETWEEN BODY IMAGE AND SELF-ACCEPTANCE IN PATIENTS UNDERGOING HEMODIALYSIS - Wijayanti, Lono; Wulan Anggraini, Mitha; Nurjanah, Siti; Umamah, Faridah (Nurse and Holistic Care, 2024)
Introduction: Hemodialysis is a medical procedure that often causes significant physical changes, such as weight loss, swelling, and skin changes that can affect the patient's body image. The long-term process of hemodialysis also has the potential to interfere with psychological conditions, especially patient self-acceptance. Objective: This study aims to determine the relationship between body image and self-acceptance in patients undergoing hemodialysis. Methods: This type of research is quantitative research with a cross-sectional approach. The population of this study were all patients undergoing hemodialysis at Sidoarjo Regional Hospital as many as 200 respondents. The sample size was 133 respondents selected using a simple random sampling technique. The independent variable is body image and the dependent variable is self-acceptance. The instrument of this study was a questionnaire. Analysis using the Spearman Rank test. Results: The results of this study indicate that 54.9% experience negative body image and 41.4% experience low self-acceptance. Based on the results of the analysis obtained a correlation coefficient of 0.601 which means it has a strong relationship with, p-value = 0.000. Conclusions: Patients who have a positive body image tend to show a higher level of self-acceptance of their physical condition.